Polyunsaturated lysophosphatidic acid as a potential asthma biomarker - Ackerman, Steven J (Biomark Med, 2016)
Lysophosphatidic acid (LPA), a lipid mediator in biological fluids and tissues, is generated mainly by autotaxin that hydrolyzes lysophosphatidylcholine to LPA and choline. Total LPA levels are increased in bronchoalveolar lavage fluid from asthmatic lung, and are strongly induced following subsegmental bronchoprovocation with allergen in subjects with allergic asthma. Polyunsaturated molecular species of LPA (C22:5 and C22:6) are selectively synthesized in the airways of asthma subjects following allergen challenge and in mouse models of allergic airway inflammation, having been identified and quantified by LC/MS/MS lipidomics. This review discusses current knowledge of LPA production in asthmatic lung and the potential utility of polyunsaturated LPA molecular species as novel biomarkers in bronchoalveolar lavage fluid and exhaled breath condensate of asthma subjects.